2014
DOI: 10.3732/ajb.1400226
|View full text |Cite
|
Sign up to set email alerts
|

Effects of functionally asexual reproduction on quantitative genetic variation in the evening primroses (Oenothera, Onagraceae)

Abstract: These results support the prediction that sexual reproduction maintains higher genetic variation within populations, which may facilitate adaptive evolution. We also found partial support for the prediction that a loss of sex leads to greater population differentiation, which may elevate speciation rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
1
4
1
Order By: Relevance
“…Consistent with the results of other studies reported earlier (Pfeiffer et al, 2012; Godfrey and Johnson, 2014), high genetic diversity was recorded in the sexually reproducing Z. neesanum and Z. nimmonii populations and the three south Kerala populations of Z. zerumbet from forest land and narrow genetic base in obligately asexual ginger and five of the seven clonal populations of Z. zerumbet from revenue land ( Table 2 ). The level of genetic diversity in two clonal populations of Z. zerumbet , ZzKTK and ZzPNR, represented an exception, which, as discussed later, can be addressed in the light of available literature.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with the results of other studies reported earlier (Pfeiffer et al, 2012; Godfrey and Johnson, 2014), high genetic diversity was recorded in the sexually reproducing Z. neesanum and Z. nimmonii populations and the three south Kerala populations of Z. zerumbet from forest land and narrow genetic base in obligately asexual ginger and five of the seven clonal populations of Z. zerumbet from revenue land ( Table 2 ). The level of genetic diversity in two clonal populations of Z. zerumbet , ZzKTK and ZzPNR, represented an exception, which, as discussed later, can be addressed in the light of available literature.…”
Section: Discussionsupporting
confidence: 92%
“…Supporting the hypotheses partly, empirical studies generally report high genetic diversity in sexuals such as Oenothera spp. (Godfrey and Johnson, 2014) and a narrow genetic base in asexuals such as Ziziphus celata (Gitzendanner et al, 2012) and Gagea spathacea (Pfeiffer et al, 2012). Although, genetic diversity is predicted to safe guard populations from infections (Rice, 2002; Keesing et al, 2010; Civitello et al, 2015), the amount of genetic diversity needed for a population to prevent disease spread is not clear (King and Lively, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although empirical evidence across Oenothera has confirmed classic predictions of decreased levels of defense with reduced sexual reproduction [44] (albeit increased diversity of flavonoid metabolites [48], our results showed less clear differences between functionally asexual PTH and sexual plants. We found that although sexual and PTH plants are well differentiated having about 30% (total) and 50% (rapidly evolving) specific gene families each, both groups had almost the same number of phenolic proteins.…”
Section: Genomic Evolution Of Plant Defense and Phenolic Metabolismcontrasting
confidence: 62%
“…The development of these molecular resources has allowed for recent advances in genetics, evolutionary biology, and systematics, and opened new interdisciplinary directions. For example, these resources allowed the first test in plants of multiple predictions stemming from theory of the evolution of sex [40,[44][45][46][47][48][49][50][51]. Recent research also led to important advances in the study of plant defense evolution [52][53][54][55][56][57][58][59], and eco-evolutionary dynamics within communities [60][61][62][63][64][65][66][67][68].…”
Section: Introductionmentioning
confidence: 99%
“…Variation in the rate of evolution for a particular trait is influenced by several factors, including the rate of sexual reproduction (Johnson et al, 2009) and the selective pressure on a particular trait. It has been argued that the longer generation time and less frequent recombination of clonal species lead to slowed genetic change and decreased rate of trait evolution (Hamilton et al, 1990;Charlesworth & Wright, 2001;Godfrey & Johnson, 2014). Additionally, generation time is negatively correlated with molecular substitution rates in angiosperms, allowing typically short-lived herbaceous species to 'explore' a wider climatic space than longer-lived species because of higher rates of evolution for climatic preference (Smith & Beaulieu, 2009).…”
Section: Rate Of Defense Evolution and Clonality Along The Climatic Nmentioning
confidence: 99%